2022
DOI: 10.1021/acs.energyfuels.2c00708
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Stabilization Mechanism of SiO2 Nanoparticles and Anionic Surfactants during Foam Fracturing

Abstract: To study the synergistic stabilization mechanism of SiO2 nanoparticles and anionic surfactants during foam fracturing, inorganic SiO2 nanoparticles and sodium dodecyl sulfate (SDS) were used as a foam stabilizer and foaming agent, respectively, to prepare foam fluids. Foam stability was analyzed by evaluating the foam volume, half-life, and morphology. The synergistic stabilization mechanism of SDS and SiO2 nanoparticles was studied by measuring and analyzing the surface tension, contact angle, and bubble diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Regarding aqueous foams with nanoparticles, or so-called Pickering foam, the improvement in foam stability can be attributed to the extremely large detachment energy of particles from the gas/liquid interface. , The wettability of particles, characterized by the contact angle, is a good indicator of the surface activity that determines the stabilizing effectiveness, and existing studies indicated that nanoparticles with a contact angle between 40 and 70° would be optimal for producing stable Pickering foam; Li et al recently reported that the ideal nanosilica contact angle for stabilizing foam is between 60 and 90°. Typically, nanoparticles are dispersed with appropriate surfactants in the foaming liquid, and the surfactant concentration always plays a significant role in modifying the surface activity of nanoparticles, whereas an excess surfactant would reduce foam stability . A major issue with nanoparticle-stabilized foam is its relatively low viscosity, which prevents it from carrying proppant for an extended period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding aqueous foams with nanoparticles, or so-called Pickering foam, the improvement in foam stability can be attributed to the extremely large detachment energy of particles from the gas/liquid interface. , The wettability of particles, characterized by the contact angle, is a good indicator of the surface activity that determines the stabilizing effectiveness, and existing studies indicated that nanoparticles with a contact angle between 40 and 70° would be optimal for producing stable Pickering foam; Li et al recently reported that the ideal nanosilica contact angle for stabilizing foam is between 60 and 90°. Typically, nanoparticles are dispersed with appropriate surfactants in the foaming liquid, and the surfactant concentration always plays a significant role in modifying the surface activity of nanoparticles, whereas an excess surfactant would reduce foam stability . A major issue with nanoparticle-stabilized foam is its relatively low viscosity, which prevents it from carrying proppant for an extended period.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, nanoparticles are dispersed with appropriate surfactants in the foaming liquid, and the surfactant concentration always plays a significant role in modifying the surface activity of nanoparticles, whereas an excess surfactant would reduce foam stability. 29 A major issue with nanoparticlestabilized foam is its relatively low viscosity, which prevents it from carrying proppant for an extended period. This is easily remedied by the addition of water-soluble polymers, and the presence of nanoparticle−polymer−surfactant micellar networks in the continuous phase may also reduce polymer amounts, thereby decreasing the risk of polymer-related reservoir damage.…”
Section: Introductionmentioning
confidence: 99%